Enhanced photocurrent generation at a spiro-OMeTAD/AuNPs-TiO2interface with grating-coupled surface plasmon excitation - Hathaithip Ninsonti (2018)
Copyright © 2015 The Institute of Electronics, Information and Communication Engineers The fabrication of a grating structure formed by a solid-state electrolyte layer on a dye-TiO2film by the nanoimprinting technique using a polydimethylsiloxane (PDMS) stamp and its application in photoelectric conversion devices are described. The PDMS grating pattern is imprinted from blu-ray disc recordable. A silver electrode was deposited on the patterned solid-state electrolyte layers. Surface plasmon resonance (SPR) excitation was observed in the fabricated solar cells by irradiation with white light. The photoelectric conversion properties were measured to study the effect of the two types of SPR excitations, i.e., the propagating surface plasmon on the Ag grating surface and the localized surface plasmon from the Au nanoparticles on TiO2.